(untitled) (Bibliouniversitas@ABRM.md, 2021)
This paper is dedicated animalistic literature in 21st century. The author deals with two short stories about cats from anthology “The Birds Market” (Mosсow, 2019). Author shows peculiarities of comic in stories “The Lion” by Oleg Osborn about small wild cat and the story of british blue cat Matthew, who lives as a pet in Helen Kolin family (“I Shall Give You Nickname Scoundrel”). The author of this paper discusses subtext, metaphor, gender characteristics, chronotope, charming sense of humor and contemporaneity of two little masterpieces.